PROSES PENYUSUNAN ANGGARAN & PENGALOKASIAN BELANJA DI PEMDA KABUPATEN WONOGIRI - H.M. Nuh Fadillah, Muhtar (UGM, 2004)
This study evaluates the budget formulation process of Wonogiri regency, including efforts to accommodate public aspiration and the roles of local parlement.